Monitoring cardiovascular changes due to local anesthesia during and after tooth extraction using pulse wave analysis. (February 2015) - Veerabhadrappa, S.T.; Vyas, Anoop Lal; Anand, Sneh; Das, Nagarajappa
Abstract: A study was conducted to determine the ongoing short-term changes in pulse waveform and pulse transit time in patients during tooth extraction. The sympathetic stimulation produced during tooth extraction under local anesthesia (LA) utilizing 2% lignocaine with adrenaline is evaluated. The increase in pulse rate due to vasoconstriction in the peripheral blood vessels has been quantifying the sympathetic stimulation to the local anesthesia. The ECG and pulse signals were recorded from 16 non-medically compromised dental patients in resting condition (before local anesthesia), 2–3 min after injection of local anesthesia and 5–10 min after tooth extraction. The amplitudes and timings of pulse, width, slope, pulse rate interval and PTT were computed for every pulse. More than 25% increase in amplitude and slope of the forward wave and about 15% decrease in rise time and the width of the forward wave were observed after injection of local anesthesia (PostLA) as compared to pre-local anesthesia (PreLA) stages. Indices utilizing the variations on pulse amplitude can provide a window to detect volume of anesthetic and vascular stiffness. It is seen that the PTT decreases more than 5% after LA and increased about 5% after surgery as compared to resting conditions (PreLA). The result suggests that the contour analysis of pulse waveform and PTT can be used to quantify the sympathetic stimulation due to local anesthesia in healthy dental patients. The variations in amplitude shall be given more efforts and attention in order to ride the challenge in developing some means of pulse contour, which can be used to assist in the monitoring of the local anesthetic volume and duration.